Image reconstruction for solid profile measurement in ERT using non-invasive approach - Yasmin, Abdul Wahab; Ruzairi, Abdul Rahim; Mohd Hafiz Fazalul, Rahiman; Leow, Pei Ling; Suzanna, Ridzuan Aw; Muhammad Jayasuman, Pusppanathan; Mohd Fadzli, Abd Shaib; Herlina, Abdul Rahim; Elmy Johana, Mohamad (Universitas Ahmad Dahlan, 2017)
Image reconstruction software and its image reconstruction algorithm are an important step towards constructing a tomography system. This paper demonstrates an image reconstruction of solid profile using linear back projection (LBP) algorithm and global threshold. A forward problem and inverse problem are discussed. The modelled of sensitivity distributions using COMSOL proved that the system is able to detect the liquid-solid regime in vertical pipe. Additionally, the location of the phantom can be easily distinguished using LBP algorithm and thresholding technique. The simulations and experiments results indicate that the sensitivity distribution of non-invasive ERT system can be applied in getting a tomogram of the medium of interest.